Dating Violence: Study with Adolescents from Heredia (Costa Rica) - Andrés Avelino Fernández-Fuertes; María Begoña Orgaz-Baz; Mariana De Lima-Silva; Manuel Arturo Fallas-Vargas; José Antonio García-Martínez (Revista Electrónica Educare)
Most of human aggressive behavior occurs in the context of a romantic relationship. Adolescents are not an exception: research show a significant prevalence of dating violence, revealing the need for further study, especially in Latin America, given the lack of research on this topic. This study aims at strengthening knowledge about aggressive behavior in adolescent dating relationships in Costa Rica, taking into account different aggressive behaviors, not only physical or sexual abuse; differences by gender are also analyzed. Based on an ex post facto design, a standardized instrument was used to measure five types of aggressive behavior (i.e., verbal-emotional, physical, sexual, relational and threats) in a sample of 468 adolescents from Heredia (Costa Rica). Results show that most participants had committed or suffered aggressions in dating relationships, especially verbal-emotional or both verbal-emotional and sexual abuse, but the mean frequency of reported aggression was low; some significant intersex differences were also found. Results obtained indicate that adolescents have difficulties to deal with conflicts in their romantic relationship; thus this problem needs to be addressed holistically in order to increase the impact of prevention programs for youth.